Is the cell wall of marine phytoplankton a protective barrier or a nanoparticle interaction site? Toxicological responses of Chlorella autotrophica and Dunaliella salina to Ag and CeO2 nanoparticles. (December 2018) - Sendra, Marta; Blasco, Julián; Araújo, Cristiano V.M.
Graphical abstract: Highlights: Toxicity of Ag and Ce on Chlorella autotrophica and Dunaliella salina was studied. Contaminants were tested in dissolved and nanoparticulate forms. Reproductive, structural and physiological effects were observed in both species. Despite being a cell wall free microalga, D . salina was less sensitive to both metals. Tolerance might be linked to metal biosorption, trapping and detoxification processes. Abstract: The use of nanoparticles (NPs), such as Ag and CeO2 NPs, has increased considerably in the last decade due to their importance for the production of engineered nanomaterials applied to new consumer products. This generalized use in everyday products has made the presence of NPs in aquatic systems more frequent and makes them potential environmental disturbers. Marine phytoplankton is at the bottom of the food web and, therefore, microalgae are potentially susceptible to NPs at different levels: reproductive (population growth), structural and metabolic. One of the first mechanisms of toxicity is caused by the adsorption of NPs onto the cell wall later leading to their internalization. As the cell wall may be a barrier against the intake of NPs, species lacking a cell wall would be expected to show a higher sensitivity. In the present study, two microalgae species with a marked structural difference, D . salina, lacking a cell wall, and Chlorella autotrophica, with a typical cellulosic cell wall, were exposed to ionic and NP forms of the metals Ag and Ce for 72 h. The biomarkers used as indicative of toxicity were: cell density, cell viability, cell size, cell complexity, autofluorescence of chlorophyll a, active chlorophyll, effective quantum yield of PII (photosystem II) and reactive oxygen species (ROS). Exposure to Ag and Ce in both ion and NP forms affected the reproductive, structural and physiological mechanisms of D . salina and C . autotrophica . In general, toxicity resulted in a decrease in active chlorophyll, effective quantum yield of PII, and cell density and an increase in cell complexity and ROS. For both species, treatments with Ag were more toxic than those of Ce and, for both metals, the ionic form was more toxic than the NPs. Although D . salina lacks a cell wall, it was more tolerant than C . autotrophica, indicating that the absence of a cell wall does not make it a more sensitive species. The higher tolerance of D . salina might be related to different processes to manage metal exposure that prevent toxicity such as biosorption, by producing extracellular polymeric substances, and the elimination of the compounds to the external environment.